2022
DOI: 10.1038/s41598-022-18924-z
|View full text |Cite
|
Sign up to set email alerts
|

Improved cognitive performance in trace amine-associated receptor 5 (TAAR5) knock-out mice

Abstract: Trace amine-associated receptors (TAARs) are a family of G protein-coupled receptors present in mammals in the brain and several peripheral organs. Apart from its olfactory role, TAAR5 is expressed in the major limbic brain areas and regulates brain serotonin functions and emotional behaviours. However, most of its functions remain undiscovered. Given the role of serotonin and limbic regions in some aspects of cognition, we used a temporal decision-making task to unveil a possible role of TAAR5 in cognitive pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…After the dimerization of TAAR1 with the dopamine receptor D2R, dopamine signaling activity shifts from the β-arrestin-2 signaling pathway to Gi activation [ 1 , 55 , 56 , 57 , 58 ]. The study of TAAR5-KO animals and TAAR5 agonist α-NETA also demonstrated effects of TAAR5 absence on dopaminergic transmission functioning, at least in the central nervous system [ 59 , 60 , 61 , 62 , 63 ]. In contrast, the role of TAAR9 in dopaminergic transmission was not described.…”
Section: Discussionmentioning
confidence: 99%
“…After the dimerization of TAAR1 with the dopamine receptor D2R, dopamine signaling activity shifts from the β-arrestin-2 signaling pathway to Gi activation [ 1 , 55 , 56 , 57 , 58 ]. The study of TAAR5-KO animals and TAAR5 agonist α-NETA also demonstrated effects of TAAR5 absence on dopaminergic transmission functioning, at least in the central nervous system [ 59 , 60 , 61 , 62 , 63 ]. In contrast, the role of TAAR9 in dopaminergic transmission was not described.…”
Section: Discussionmentioning
confidence: 99%
“…This relationship is confirmed by the altered cognitive profile of TAAR5-KO. TAAR5-KO mice showed fewer errors, better execution speed, and higher learning progress [ 113 ].…”
Section: The Family Of Taars—a New Target For Depression Therapy?mentioning
confidence: 99%
“…Notably, recent studies found that mTAAR5 is expressed in the major limbic brain areas and is involved in the regulation of emotional behavior, suggesting that TAAR5 antagonism may represent a novel therapeutic strategy for anxiety and depression. 13,17,29,30 Moreover, a correlation between mTAAR5 with adult neurogenesis and dopamine transmission, and its involvement in sensorimotor functions and cognitive processes have been suggested. 17,29−31 The limited knowledge of the druglike ligand space of TAAR5 modulators impairs potential TAAR5-targeted drug discovery campaigns.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Murine subtypes are the best characterized among mammals in terms of the number of ligands. , For the mouse TAAR5 (mTAAR5), both agonists (that is trimethylamine, a sexually dimorphic mouse odor secreted into urine, ,, and alpha-NETA, an acetylcholine esterase inhibitor) and antagonists (two 5-HT 1A ligands) are known. Notably, recent studies found that mTAAR5 is expressed in the major limbic brain areas and is involved in the regulation of emotional behavior, suggesting that TAAR5 antagonism may represent a novel therapeutic strategy for anxiety and depression. ,,, Moreover, a correlation between mTAAR5 with adult neurogenesis and dopamine transmission, and its involvement in sensorimotor functions and cognitive processes have been suggested. , The limited knowledge of the druglike ligand space of TAAR5 modulators impairs potential TAAR5-targeted drug discovery campaigns. Thus, the discovery of additional ligands is a crucial step in gaining a mechanistic and physiological understanding of TAAR5.…”
Section: Introductionmentioning
confidence: 99%